Competition between Asian Network Airlines and Low-Cost Carriers: Strategic Analysis. Issue 1 (January 2015) - Pearson, James; O'Connell, John F.; Pitfield, David E.; Ryley, Tim
Asia Pacific is increasingly at the forefront of world aviation, and low-cost carriers (LCCs) there now have 26% of all seats. This amount rises to 57% in Southeast Asia and 56% in South Asia. Clearly, Asian network airlines are very exposed to LCCs, and there are many consequences, such as lower financial performance from inadequately meeting the expectations of customers, offering insufficient value for money, and customer dissatisfaction. It is crucial that Asian network airlines respond expeditiously and appropriately to LCCs. This paper looks at the strategic capability of 22 Asian network airlines in competing with LCCs on the basis of analyzing questionnaire data from these airlines with respect to the level of importance and difficulty of 37 competitive responses across six response categories. Fundamentally, this paper concerns only their capability in competing with LCCs and does not consider their overall strength. This paper also identifies the importance and difficulty of all 37 responses and how the response categories vary by airline, while linking strategic capability with profit margins. The results show that strategic capability varies widely, with Vietnam Airlines possessing the strongest strategic capability and SilkAir, the weakest. Of airlines that compete heavily with LCCs, Garuda Indonesia has strong capability, while Thai Airways and Philippine Airlines do not. For all 22 Asian network airlines, quickly introducing changes, leveraging brand strength, and increasing aircraft use are the most important responses, and there is a reasonably strong correlation between strategic capability and margin, suggesting that those airlines with strong capabilities should achieve higher margins.